2004
DOI: 10.1161/01.res.0000148635.73331.c5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment With Allopurinol Boosts Survival and Cardiac Contractility in Murine Postischemic Cardiomyopathy

Abstract: Abstract-Oxidative stress is a hallmark of systemic illnesses, including heart failure. Nevertheless, the overall importance of radical production in the heart remains conjectural; is it merely a marker of illness, or can intervention alter the progression of disease? This question was addressed by blocking xanthine oxidase (XO), a superoxide-generating enzyme that is upregulated in animal models of heart failure. In a randomized prospective trial design, we administered the XO inhibitor allopurinol orally to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
99
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 39 publications
9
99
1
Order By: Relevance
“…24 It is important to note, however, that in all these experimental models of heart failure, the beneficial effects of XO inhibition were achieved because XO activities were increased within the myocardium; treatment with either allopurinol or oxypurinol restored XO activity to baseline levels and myocardial function was restored. 19,21,22,[25][26][27] These findings, therefore, suggest that by limiting oxidant stress to maintain levels of ROS required for ambient signaling, XO inhibition abrogates the destructive effects of ROS on various intracellular mechanisms that maintain function and integrity in the working cardiomyocyte. In addition, it has also been suggested that decreases in uric acid levels seen with XO inhibition have an antiinflammatory effect on the cardiovascular system.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…24 It is important to note, however, that in all these experimental models of heart failure, the beneficial effects of XO inhibition were achieved because XO activities were increased within the myocardium; treatment with either allopurinol or oxypurinol restored XO activity to baseline levels and myocardial function was restored. 19,21,22,[25][26][27] These findings, therefore, suggest that by limiting oxidant stress to maintain levels of ROS required for ambient signaling, XO inhibition abrogates the destructive effects of ROS on various intracellular mechanisms that maintain function and integrity in the working cardiomyocyte. In addition, it has also been suggested that decreases in uric acid levels seen with XO inhibition have an antiinflammatory effect on the cardiovascular system.…”
mentioning
confidence: 93%
“…On a functional level, there is strong evidence that XO inhibition enhances the responsiveness of the myofilaments to calcium. 21 The study by Minhas et al additionally shows that XO inhibition enhanced SERCA2a levels while decreasing expression of the sodium-calcium exchanger to increase contractility. 24 It is important to note, however, that in all these experimental models of heart failure, the beneficial effects of XO inhibition were achieved because XO activities were increased within the myocardium; treatment with either allopurinol or oxypurinol restored XO activity to baseline levels and myocardial function was restored.…”
mentioning
confidence: 97%
See 3 more Smart Citations